A new discrete element-embedded finite element method for transient deformation, movement and heat transfer in packed bed. (February 2021) - Liu, Xu; Gui, Nan; Yang, Xingtuan; Tu, Jiyuan; Jiang, Shengyao
Highlights: Embedded discrete element is proposed to compute force & heat transfer of particles DEFEM realizes coupled simulation of deformation, movement & heat transfer of solids DEFEM combines FEM and DEM, and avoids overlapping and penetration of meshes DEFEM supports parallel computing and three times faster than a pure FEM solution Particle deformation and heat transfer in packed layers are simulated and discussed. Abstract: A new discrete element-embedded finite element method (DEFEM) scheme is proposed here, which solves the contact force and heat conduction of particles with embedded discrete elements (EDE), employs the finite element method (FEM) to get the deformation and internal temperature change of particles with heat and stress on the boundary and employs the discrete element method (DEM) to obtain the movement of particles. The DEFEM is characterized by coupling the deformation, motion and heat conduction of particles .Compared to either merely DEM or pure FEM, DEFEM combines the solution ideas of the FEM and DEM, and avoids the problem of overlapping and penetration of mesh elements in FEM. DEFEM also supports parallel computing, which is about three times faster than a pure FEM solution. As a demonstration, we developed an in-house code to perform DEFEM to simulate the extrusion and heat conduction of packed pebble bed, in comparison with a pure FEM solution for reference. Based on the numerical results, the characteristics of particle deformation and heat transfer in different extrusion speeds and layers are discussed.